Designing Politics: Designing Respect-poder e alteridades dentro de parcerias cultuais internacionais - Laura Burocco (Ciências Sociais Unisinos)
Using as a starting point the experience of direct participation in the Designing Politics: Design- ing Respect challenger promoted by the international partnership Theatrum Mundi in Rio de Janeiro, the article intends to highlight the practices of culture privatization fomented by the local partners of the initiative in the territory of Porto Maravilha, as well as the power relations and institutional marketing involved in these forms of international cultural partnerships.